Ethnonationalism and Humanitarian Diplomacy: A Study on the Indigenous Papuan Response to Vanuatu’s Advocacy for Papuan Independence - Permana, Aditya; Awatarino, Muhammad (Universitas Muhammadiyah Ponorogo, 2024)
Papua Province’s integration into the Unitary State of the Republic of Indonesia (NKRI) has been marked by historical intricacies, particularly stemming from the prolonged process that spans approximately 14 years. Commencing with the Round Table Conference in 1949 and culminating in the 1969 People’s Opinion (PEPERA), Papua’s trajectory has been shaped by political dynamics and challenges related to national integration. This paper delves into the complexities surrounding Papua’s integration, exploring the impact of the New York Agreement, the PEPERA process, and its subsequent implications for the region’s sociopolitical landscape. Drawing attention to the contested legitimacy of the PEPERA process, we examine the dynamics that have contributed to the ongoing conflict in Papua, with indigenous Papuans expressing disillusionment over perceived marginalization and discrimination. In light of these challenges, the emergence of ethnonationalism becomes a focal point, exacerbated by state policies that have further marginalized indigenous populations during periods such as the New Order era and the declaration of Military Operations Area (DOM) status. Central to our inquiry is an exploration of the response of the Indigenous Papuan community to the advocacy for Papuan humanitarian diplomacy by Vanuatu, a prominent member of the United Liberation Movement for West Papua (ULMWP). This study aims to investigate the extent to which the Orang Asli Papua (OAP) or Indigenous Papuan community’s response aligns with the values inherent in the concept of ethnonationalism. By addressing these issues, we seek to contribute to the scholarly understanding of ethnonational dynamics, humanitarian diplomacy, and the ongoing sociopolitical landscape in Papua.